Prevalence of Nonsuicidal Self-Injury in Nonclinical Samples: Systematic Review, Meta-Analysis and Meta-Regression - Swannell, Sarah V.; Martin, Graham E.; Page, Andrew; Hasking, Penelope; St John, Nathan J. (Suicide & life-threatening behavior, 2014)
Published prevalence estimates of nonsuicidal self‐injury (NSSI) among nonclinical samples are highly heterogeneous, raising concerns about their reliability and hindering attempts to explore the alleged increase in NSSI over time. Accordingly, the objectives of this study were to investigate the influence of methodological factors on heterogeneity in NSSI prevalence estimates, explore changes over time, and estimate overall international NSSI prevalence. Results showed that methodological factors contributed over half (51.6%) of the heterogeneity in prevalence estimates, and, after adjusting for these factors, NSSI prevalence did not increase over time. Overall, pooled NSSI prevalence was 17.2% among adolescents, 13.4% among young adults, and 5.5% among adults. Clearly, development of standardized methodology in NSSI research is crucial if accurate estimates are desired.